Influence of second phases on fatigue crack growth behavior of nickel aluminum bronze. (January 2016) - Xu, Xiaoyan; Lv, Yuting; Hu, Meng; Xiong, Di; Zhang, Lefu; Wang, Liqiang; Lu, Weijie
Highlights: Fatigue crack propagates through α/κII interface with accelerating the growth rate. Fatigue crack propagates through hard brittle κIII phase with cleavage fracture. Second cracks formed along α/κIII interfaces slow down the fatigue crack growth rate. Fatigue striations formed in α grains improves the fatigue crack growth resistance. Abstract: The influence of phases with different morphology and mechanical properties on fatigue crack growth behavior in nickel aluminum bronze (NAB) has been investigated. Annealing at 675 °C and normalizing at 920 °C heat treatments were used to produce different morphologies and fractions of second phases. This analysis shows that the coarse dendritic κII particles and κIII lamellae as hard brittle phases in as-cast and annealed NAB have an accelerative effect on the fatigue crack propagation where by cracks propagate through α and κII /κIII interface. Fatigue cracks in normalized NAB prefer to propagate through the ductile α grains, form fatigue striations and have the lowest crack growth rate. The uniformly distributed, fine κIV precipitates in the α grains improves fatigue crack growth resistance. This work identifies the role of NAB second phases on propagation of fatigue cracks, and provides suitable heat treatment for improving fatigue crack resistance in terms of controlling second phase type, distribution and percentage.